Educational challenges for children with special needs in inclusive primary schools - Chairunnisa, Connie; Rismita, Rismita (Jurnal Ilmiah Sekolah Dasar, 2022)
There is no specific curriculum for inclusive students, and there is also no assessment guide for inclusive students. It causes students with special needs to have difficulty learning, and learning does not run optimally. This study aimed to analyze the learning completeness of ABK students in inclusive elementary schools and various challenges in managing inclusive schools. This type of research is qualitative. The method used in this study is a qualitative method with phenomenology. The design used in this study using Miles and Huberman. The subjects in this study amounted to 8 people. Methods of data collection using the method of observation, interviews, and triangulation. The research instrument is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis. The data analysis method uses framing analysis. The research method used is the descriptive qualitative method with framing analysis. The results of this study are that first, the learning completeness of ABK students is still not optimal. Second is the unpreparedness of the teacher in teaching ABK students. Third, the limitations of special assistant teachers for inclusive students. Fourth, inadequate facilities and infrastructure for inclusive students. Fifth, there are differences in perceptions of ABK students between schools, the community and the government. The general conclusion is that students with special needs learning mastery will succeed if there is a common perception between inclusive schools, the environmental community and the local government.